2020
DOI: 10.3390/w12092515
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Nitrogen and Phosphorus Cycles in a Timber Reef Deployment Area

Abstract: In an oligotrophic bay, Mitsu Bay, Japan, artificial timber reefs (ATRs) are deployed to increase fish production. In such man-made ecosystems, the biological activities of other organisms as well as the physical structures of ATRs could influence nutrient cycling. A pelagic–benthic coupling model expressing both phosphorus and nitrogen cycling was developed to investigate seasonal variation in the associated nutrients and their annual budget in the ATR areas and the entire bay system. The model consists of eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Similar to other experimental studies introducing geogenic or biogenic hard substrates into soft-sediment coastal ecosystems (Alam et al, 2020) we found that the tree-reefs quickly developed into hotspots of sessile epibenthos biodiversity. Notably, we found a clear vertical zonation of species over the reefs' vertical gradient.…”
Section: The Advantageous Effect Of Tree-reef Height On Sessile Organ...supporting
confidence: 89%
See 3 more Smart Citations
“…Similar to other experimental studies introducing geogenic or biogenic hard substrates into soft-sediment coastal ecosystems (Alam et al, 2020) we found that the tree-reefs quickly developed into hotspots of sessile epibenthos biodiversity. Notably, we found a clear vertical zonation of species over the reefs' vertical gradient.…”
Section: The Advantageous Effect Of Tree-reef Height On Sessile Organ...supporting
confidence: 89%
“…Historically, large wood has been removed from river systems globally (Nagayama and Nakamura, 2010) though it is well documented that large woody debris creates excellent habitat for fish in aquatic systems (McMahon and Holtby, 1992) such as rivers, lakes, and estuaries. This is also found to be the case in marine environments (Gonor et al, 1988;Masuda et al, 2010;Alam et al, 2020). However, studies on the effect of large woody debris on fish and sessile life in marine systems are very limited in comparison with studies on the biological effect of wood in riverine and estuarine environments.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…If the discharge exceeds the standard, the balance of the water body will be destroyed, resulting in rapid algae and plankton growth in the water body. The decrease in concentration and the death of fish and shrimp in a large area will eventually worsen the water quality, thus affecting human production activities in the ocean [59].…”
Section: Research On the Detection Of Nitrate Nitrogen In Watermentioning
confidence: 99%